Picture Cards Game: The Strategy to Facilitate Differentiated Learning in Teaching English Writing Skills for Young Learners - Wulandari, Putri; Sari, Valentina Dyah Arum (Universitas Pahlawan Tuanku Tambusai, 2024)
Developing strong writing skills is essential for young students. This research investigates the implementation of picture card games as a tool to facilitate differentiated learning in writing instruction. This study explored how picture card games can be adapted to meet the diverse needs and abilities of young students. It examines the effectiveness of this approach in improving writing skills, including vocabulary and sentence structure. It also explored the impact of picture card games on students' engagement and motivation in writing activities. This study explored the potential of picture card games as a learning tool in middle school located in Dlingo, Yogyakarta. This study investigated the use of mixed methods to understand students' experiences with the use of picture card games. This study used a mixed methods approach, which combined quantitative and qualitative data collection techniques. In the quantitative aspect, this study used questionnaires to collect data from a group of seventh grade students consisting of 32 students. These questionnaires tended to ask closed questions with pre-determined answer options, which allowed this study to collect numerical data on students' perceptions. The findings showed a moderately successful implementation (76%) of picture card games, suggesting a positive student response and contribute to the understanding of different learning strategies and their potential to improve students' writing skills in a fun and engaging way. Additionally, with a moderate rating of 77.3%, the study confirmed the benefits associated with using picture card games for English vocabulary learning. The findings suggest that there are still possibilities for improvement to maximize the potential of the picture card game.